The lure of authority: Motivation and incentive effects of power - Ernst Fehr; Holger Herz; Tom Wilkening (Institute for the Study of Labor (IZA), 2012)
Authority and power permeate political, social, and economic life, but empirical knowledge about the motivational origins and consequences of authority is limited. We study the motivation and incentive effects of authority experimentally in an authority-delegation game. Individuals often retain authority even when its delegation is in their material interest - suggesting that authority has non-pecuniary consequences for utility. Authority also leads to over-provision of effort by the controlling parties, while a large percentage of subordinates under-provide effort despite pecuniary incentives to the contrary. Authority thus has important motivational consequences that exacerbate the inefficiencies arising from suboptimal delegation choices.
Keywords: C92; D83; D23; 330; organizational behavior; incentives; experiments and contracts; Verhalten in Organisationen; Autorität; Leistungsmotivation; Test